Asymmetric Risk Spillover of the International Crude Oil Market in the Perspective of Crude Oil Dual Attributes - Jia, Shuaishuai; Dong, Hao; Yang, Haowen (Frontiers in Environmental Science, 2021)
The heterogeneity of investor sentiment plays the key role in causing the asymmetry of information transmission pattern and transmission intensity between markets. This paper analyzes the asymmetric risk spillover between the international crude oil market and other markets, including commodity market and financial market, using monthly data from June 2006 to October 2020. Risk from the international crude oil market is separated into upside and downside risks. The empirical results suggest that, first, from the perspective of static spillover, the risk spillover between the international oil market and other markets enhances significantly in response to rising return; second, from the perspective of dynamic spillover, the asymmetric risk spillover of international crude oil market manifests the key roles played by important events happened in crude oil market and alternating attributes of crude oil. Some policy suggestions are proposed in light of these empirical results